2012
DOI: 10.1038/mp.2012.37
|View full text |Cite
|
Sign up to set email alerts
|

Convergent functional genomics of schizophrenia: from comprehensive understanding to genetic risk prediction

Abstract: We have used a translational convergent functional genomics (CFG) approach to identify and prioritize genes involved in schizophrenia, by gene-level integration of genome-wide association study data with other genetic and gene expression studies in humans and animal models. Using this polyevidence scoring and pathway analyses, we identify top genes (DISC1, TCF4, MBP, MOBP, NCAM1, NRCAM, NDUFV2, RAB18, as well as ADCYAP1, BDNF, CNR1, COMT, DRD2, DTNBP1, GAD1, GRIA1, GRIN2B, HTR2A, NRG1, RELN, SNAP-25, TNIK), br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
313
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 374 publications
(323 citation statements)
references
References 286 publications
5
313
0
5
Order By: Relevance
“…Examination of the cumulative effects of inheriting multiple risk alleles—each of which are significantly or nominally associated with disease risk—has been able to powerfully differentiate groups of cases from controls in independent population‐based studies [Purcell et al, 2014, 2009; Patel et al, 2010; Ayalew et al, 2012; Terwisscha van Scheltinga et al, 2012]. However, despite phenotypic aggregation within families [McGuffin et al, 2003; Lichtenstein et al, 2009], no studies have so far examined polygenic risk incorporating these common genetic factors in a family context in adults, with only one group to date reporting on polygenic risk in adolescent offspring of individuals with BP [Whalley et al, 2012, 2013].…”
Section: Introductionmentioning
confidence: 99%
“…Examination of the cumulative effects of inheriting multiple risk alleles—each of which are significantly or nominally associated with disease risk—has been able to powerfully differentiate groups of cases from controls in independent population‐based studies [Purcell et al, 2014, 2009; Patel et al, 2010; Ayalew et al, 2012; Terwisscha van Scheltinga et al, 2012]. However, despite phenotypic aggregation within families [McGuffin et al, 2003; Lichtenstein et al, 2009], no studies have so far examined polygenic risk incorporating these common genetic factors in a family context in adults, with only one group to date reporting on polygenic risk in adolescent offspring of individuals with BP [Whalley et al, 2012, 2013].…”
Section: Introductionmentioning
confidence: 99%
“…The gene coding for 5-HT2A (HTR2A, 13q14-21) has been weakly associated with schizophrenia (Ayalew et al, 2012;Collins et al, 2012;Sanders et al, 2008). Other investigations have linked genetic variation within HTR2A to response to antipsychotics (Arranz et al, 1998;Chen et al, 2009;Masellis et al, 1998;Olajossy-Hilkesberger et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Using a convergent functional genomics approach, which utilizes poly-evidence scoring and pathway analyses, Ayalew et al identified several genes involved in SCZ, including DISC1 and TCF4 [32] . By combining gene expression profi ling and GWAS data, Luo et al showed that CAMKK2 is differentially expressed in SCZ and controls, and a marker in the gene, rs1063843, is associated with the expression and diagnosis of SCZ in a large GWAS dataset [33] .…”
Section: Common Variants Contributing To Sczmentioning
confidence: 99%